2021
DOI: 10.1093/gji/ggab425
|View full text |Cite
|
Sign up to set email alerts
|

Slow slip events precursory to the 2014 Iquique Earthquake, revisited with long-base tilt and GPS records

Abstract: The M=8.1, April 1st, 2014 Iquique earthquake, which broke part of the northern Chile seismic gap, was preceded by a strong foreshock sequence starting early January 2014.The reported analysis of the continuous records of the nearby GPS stations from the IPOC North Chili array lead to contradictory results concerning the existence and location of slow slip events (SSE) on the interplate contact. Resolving this controversy is an important issue, as although many SSEs are reported in subduction zones, only a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…These can have variable duration and potentially be recurrent, as in the region of Copiapo (Klein et al, 2018). In some cases, they can precede earthquakes and contribute to the initiation of the main shock rupture, as for the 2014 Iquique earthquake (Ruiz et al, 2014, Socquet et al, 2017, Boudin et al, 2021 or the 2017 Valparaiso earthquakes (Ruiz et al, 2017). Some observed transient signal remain hard to relate to any known sources.…”
Section: Transient Deformationmentioning
confidence: 99%
“…These can have variable duration and potentially be recurrent, as in the region of Copiapo (Klein et al, 2018). In some cases, they can precede earthquakes and contribute to the initiation of the main shock rupture, as for the 2014 Iquique earthquake (Ruiz et al, 2014, Socquet et al, 2017, Boudin et al, 2021 or the 2017 Valparaiso earthquakes (Ruiz et al, 2017). Some observed transient signal remain hard to relate to any known sources.…”
Section: Transient Deformationmentioning
confidence: 99%
“…However, Boudin et al (2019) argue that adding to the GNSS data a tilt records from Santa Rose, Chile (∼8 km north-east of the station IQQE) changes the spatio-temporal resolution in such a way that it rules out the occurrence of a slow-slip event with magnitude larger than 6.6 near the epicenter of the future mainshock. Instead, adding the tilt records suggests that the slow-slip activity occurs more to the south (around 20.5 • S) compared to what we have identified in this study (around 20.0 • S ).…”
Section: The Main Phase Of Aseismic Slipmentioning
confidence: 99%
“…To test the sensitivity of the tilt records with respect to the slow-slip event from this study, we have computed the amount of tilt generated by the family of models for our slow-slip event (see Supplementary Materials S3). The main difference with Boudin et al (2019) is that the computation of the tilt is done using a layered velocity model for the region, the same that we have used to obtain our models. Our findings suggest that the final amplitude of the tilt generated by the slow-slip event from this study barely exceeds the noise level reported by Boudin et al (2019) -48 and 42 nrad for the north and east components, respectively.…”
Section: The Main Phase Of Aseismic Slipmentioning
confidence: 99%
See 2 more Smart Citations